Poland : The Path to a Market Economy - Christofides, Charalambos; Ebrill, Liam.; Mylonas, Paul.; Otker, Inci. (Washington, D.C. : International Monetary Fund, 1994)
Poland's economy rebounded dramatically in 1992-93, several years after the nation embarded on a comprehensive program of economic transformation. This paper describes Polan's steps in the areas of public finance, monetary policy and financial sector reform, trade and exchange rate policy, and microeconomic liberalization, as well as the social impact of transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet